High-Power KTiOAsO4 Optical Parametric Oscillator at 300 Hz - Tao Li; Jun Meng; Gaoyou Liu; Zhaojun Liu (Photonics)
A high-power and high-repetition KTiOAsO4 (KTA) optical parametric oscillator (OPO) was established in this study, with the adoption of plane-parallel and ring cavities. The pump was a high-power Nd:YAG master oscillator power amplifier (MOPA) system with a pulse repetition frequency (PRF) of 300 Hz, and the corresponding beam quality factors were Mx2 = 3.4 and My2 = 3.2. In the plane-parallel cavity experiment, powers of 51.1 W (170 mJ) and 15.9 W (53 mJ) in the signal and idler were obtained, respectively. In terms of the average power of 1 μm of a pumped KTA OPO, to our knowledge, this is the highest average power for KTA OPO. The ring cavity was constructed to achieve lasers with both high power and beam quality. The output powers of the ring cavities for the signal and idler were 33.9 W (113 mJ) and 8.7 W (29 mJ), respectively, and the corresponding beam quality factors of the signal were Mx2 = 5.3 and My2 = 7.9. The 300 Hz 100 mJ class 1.54 μm laser with a beam quality factor of less than 10 is an ideal eye-safe light detection and ranging (LiDAR) source.